Article Overview : Deep Vein Thrombosis - Sri Meutia; Ahmad Roqyal (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Deep vein thrombosis (DVT) is an occurrence of blood clot (thrombus) formation in the deep veins, most commonly affecting the veins in the legs and arms that lead to the heart. A prospective multicenter cohort study in China involving 862 hospital-based patients with acute stroke showed an overall DVT incidence of 12.4% within 2 weeks after acute stroke. The objective of this article is to comprehensively understand DVT. The methods employed include a systematic summary of information from 15 data sources to provide insights into DVT, covering aspects such as Definition, Etiology, Epidemiology,Classification, Pathogenesis, Clinical Manifestations, Diagnosis, and DVT management